2014
DOI: 10.3389/fpsyg.2014.00549
|View full text |Cite
|
Sign up to set email alerts
|

Functional asymmetry and effective connectivity of the auditory system during speech perception is modulated by the place of articulation of the consonant- A 7T fMRI study

Abstract: To differentiate between stop-consonants, the auditory system has to detect subtle place of articulation (PoA) and voice-onset time (VOT) differences between stop-consonants. How this differential processing is represented on the cortical level remains unclear. The present functional magnetic resonance (fMRI) study takes advantage of the superior spatial resolution and high sensitivity of ultra-high-field 7 T MRI. Subjects were attentively listening to consonant–vowel (CV) syllables with an alveolar or bilabia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
(83 reference statements)
2
4
0
Order By: Relevance
“…Specifically, stops are preferentially computed on the left and non-stops on the right auditory cortex (Gage et al, 1998 ), especially when attention is required by listeners (Poeppel et al, 1996 ). This is in line with a recent 7T fMRI study that found stronger left lateralized activation for alveolar stops than labials (Specht et al, 2014 ). Crucially, none of the N1m studies was successful in proving different hemispheric processing for the different VOTs in voiced and voiceless consonants.…”
Section: N1m Hemispheric Asymmetries For Vowels Consonants and Syllsupporting
confidence: 92%
See 1 more Smart Citation
“…Specifically, stops are preferentially computed on the left and non-stops on the right auditory cortex (Gage et al, 1998 ), especially when attention is required by listeners (Poeppel et al, 1996 ). This is in line with a recent 7T fMRI study that found stronger left lateralized activation for alveolar stops than labials (Specht et al, 2014 ). Crucially, none of the N1m studies was successful in proving different hemispheric processing for the different VOTs in voiced and voiceless consonants.…”
Section: N1m Hemispheric Asymmetries For Vowels Consonants and Syllsupporting
confidence: 92%
“…The auditory areas are characterized by a layout that is highly specialized in analyzing different aspects of the signal: the primary auditory cortex (A1) seems engaged in the acoustic processing of the signal, while the superior temporal gyrus (STG) and the superior temporal sulcus (STS) work smoothly for encoding the acoustic patterns onto phonological features (Scott and Johnsrude, 2003 ; Santoro et al, 2014 ; for the speech perception and production link see Hickok and Poeppel, 2007 ; Rauschecker and Scott, 2009 ; Cheung et al, 2016 ). However, the localization and the lateralization of the structures engaged in the phonological encoding remain subjects of debate (McGettigan and Scott, 2012 ; Scott and McGettigan, 2013 ; Specht, 2013 ; Specht et al, 2014 ; Talavage et al, 2014 ; see also Cogan et al, 2014 ). Most importantly for the purpose of this work, the processing that leads speech sounds to be computed and represented within the auditory cortex is yet not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…This proposal is consistent with a number of lines of evidence. The locus of the LH high-β peak is consistent with the region in which categorical phoneme perception has been demonstrated in fMRI (e.g., Specht, Baumgartner, Stadler, Hugdahl, & Pollmann, 2014; see Turkeltaub & Branch Coslett, 2010 for a review).…”
Section: Discussionsupporting
confidence: 77%
“…The relation of structural and functional asymmetries was also the topic of review article that investigated the cortical microstructural basis of lateralized cognition (Chance, 2014 ). Moreover, several authors investigated auditory lateralization (e.g., Specht et al, 2014 ). For example, Hirnstein et al ( 2014a ; Erratum in Hirnstein et al, 2014b ) investigated how language lateralization measured with the Dichotic Listening Task relates to cognitive performance.…”
mentioning
confidence: 99%